PERANCANGAN SISTEM INFORMASI AKADEMIK MAHASISWA BERBASIS WEB DENGAN FRAMEWORK CODIGIGNITER: Studi Kasus pada Universitas Efarina - Gultom, Farida; Ginting, Wita Clarisa; Sinurat, Michael Stevano; Riswan, M. (Universitas Methodist Indonesia, 2023)
Higher education is a formal education facility that has the best service for all students. In service delivery, the use of information technology in manipulating academic data will provide great benefits to its application. Therefore, in order to help process academic data at the University, a web-based student academic information system is needed, so that it can provide fast and efficient data processing. In this study, the authors used the waterfall method to help design a system. The information processed includes information about student data, lecturer data, schedules, grades, rooms, levels, and course data. The software used is a database, as data storage media MySQL, PHP, CSS (Cascading Style Sheet), Java Script as a programming language and BootStrap is used in interface design, which aims to assist the University in processing academic data.